Super (a; d)-edge Antimagic Total Labeling of Shack(F6; B2; n) Graph for Developing a Polyalphabetic Cryptosystem - Arnasyitha Yulianti Soelistya; Dafik Dafik; Arif Fatahillah (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2020)
A graph G of order p and size q is called an (a; d)-edge-antimagic total if there exist a bijection f : V (G) [ E(G) ! f1; 2; : : : ; p + qg such that the edge-weights, w(uv) = f(u) + f(v) + f(uv); uv 2 E(G), form an arithmetic sequence with ¯rst term a and common di®erence d. Such a graph is called super if the smallest possible labels appear on the vertices. In this paper we study a super edge-antimagic total labeling of Shackle (F6; B2; n) Graph connected and we will use it to develop a polyalphabetic cryptosystem.